Carbon fiber reinforced heat-conducting phase-change composite material and preparation method thereof

By adding phase change materials and other components to the carbon fiber felt, carbon fiber reinforced thermal phase change composite materials were prepared, which solved the problem of insufficient thermal conductivity and stability of traditional phase change materials, and achieved efficient thermal management performance and was suitable for high power Integrated circuits and other high-end electronic devices.

CN119505825APending Publication Date: 2025-02-25HANGZHOU KAIKEN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411709668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional phase change materials have problems such as low thermal conductivity, poor thermal stability, and easy leakage in high-power integrated circuit heat dissipation applications, which cannot meet the needs of efficient thermal management.

Method used

Using carbon fiber reinforced thermal phase change composite material, the carbon fiber felt is added by adding phase change material, thermoplastic elastomer, antioxidant and spherical alumina, and prepared by vacuum or high pressure auxiliary infusion method at high temperature to form a good machinery with high thermal conductivity Composite materials with performance and high reliability.

Benefits of technology

It significantly improves the thermal conductivity, mechanical properties and stability of the materials, effectively solves the pumping and creep problems of traditional PCM, meets the heat dissipation needs of high-power integrated circuits, and has wide application potential in servers, communications, military industry, and aerospace. and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505825A_ABST
    Figure CN119505825A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, in particular to a carbon fiber reinforced heat-conducting phase-change composite material which comprises a carbon fiber felt, a phase-change material, a thermoplastic elastomer, an antioxidant and spherical aluminum oxide. The carbon fiber reinforced heat-conducting phase-change composite material prepared by the method has the advantages of high heat conductivity, high tensile stress, compressibility, high reliability and the like, has no obvious pumping-out and creep problems after being used as a thermal interface material for a long time, and can be applied to the fields of high-power integrated circuit heat dissipation, servers, communication, military industry, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal interface materials, and in particular to a carbon fiber reinforced thermally conductive phase change composite material. Background Art

[0002] With the rapid development of modern electronic technology, the heat dissipation problem of high-power integrated circuits has become increasingly prominent, and an urgent need has been put forward for efficient thermal management materials. Traditional thermal interface materials can no longer meet the growing demand for heat dissipation, especially in the fields of servers, communication equipment, military industry, and aerospace, which have extremely high requirements for the thermal conductivity, mechanical properties, and long-term stability of materials. Phase change materials (PCM) are regarded as potential thermal management materials due to their high energy storage density and isothermal energy storage characteristics. However, the common problems of low thermal conductivity, poor thermal stability, and easy leakage of PCM limit its widespread promotion in practical applications. Summary of the invention

[0003] In view of the above-mentioned shortcomings of the prior art, the present invention provides a carbon fiber reinforced thermally conductive phase change composite material and a preparation method thereof. The composite material has high thermal conductivity, high tensile stress, good compressibility and high reliability, and can effectively solve the problems of low thermal conductivity, poor thermal stability, and easy leakage of traditional phase change materials (PCM) in high-power integrated circuit heat dissipation applications.

[0004] Technical Solution

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0006] The invention provides a carbon fiber reinforced thermal conductive phase change composite material, which comprises carbon fiber felt, phase change material, thermoplastic elastomer, antioxidant and spherical aluminum oxide.

[0007] Furthermore, the carbon fiber felt is made of high thermal conductivity carbon fiber soft felt, and the carbon fiber diameter in the high thermal conductivity carbon fiber soft felt is 1 to 100 um and the density is 0.1 to 1 g / cm 3 The carbon fiber soft felt is preferably a carbon fiber soft felt VU-SF-HP produced by Hangzhou Weiken New Material Technology Co., Ltd.

[0008] Furthermore, the phase change material includes at least one or more of paraffin, microcrystalline paraffin, stearic acid, and octadecylamine.

[0009] Furthermore, the thermoplastic elastomer includes one or more of polyurethane, polyolefin elastomer, polystyrene elastomer, and polyamide elastomer.

[0010] Furthermore, the antioxidant includes one or more of antioxidant AT-10, antioxidant 168, antioxidant 1010 and antioxidant 1076.

[0011] Furthermore, the composite material comprises, by weight, 20-120 parts of carbon fiber felt, 10-40 parts of phase change material, 0.5-5 parts of thermoplastic elastomer, 0.05-5 parts of antioxidant, and 10-70 parts of spherical alumina.

[0012] Preferably, in parts by weight, the composite material comprises 90-110 parts of carbon fiber felt, 25-35 parts of phase change material, 1-3 parts of thermoplastic elastomer, 0.1-2 parts of antioxidant, and 40-60 parts of spherical alumina.

[0013] Most preferably, the composite material comprises, by weight, 30 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 50 parts of spherical alumina (10 um in diameter).

[0014] Furthermore, the size of the spherical alumina is 1-40 um in diameter.

[0015] A method for preparing a carbon fiber reinforced thermal conductive phase change composite material, the preparation steps comprising:

[0016] S1: mixing phase change material, polyolefin elastomer, antioxidant and thermal conductive filler aluminum oxide in a certain proportion at high temperature to prepare a premixed liquid;

[0017] S2: After compressing the carbon fiber soft felt by 30-50%, the premixed liquid is infused into the compressed carbon fiber soft felt by using a vacuum or high pressure assisted infusion method at high temperature;

[0018] S3: further compressing the poured soft felt to 10-30% of its original size at high temperature;

[0019] S4: After cooling to room temperature, releasing the compression mold to obtain a carbon fiber reinforced thermal conductive phase change composite material.

[0020] Furthermore, in steps S1, S2 and S3, the high temperature is the melting point of the phase change material and the viscosity flow temperature of the thermoplastic elastomer; the high temperature range is 70-180°C.

[0021] Preferably, a carbon fiber reinforced thermal conductive phase change composite material, the preparation steps of which include:

[0022] S1: 30 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 50 parts of spherical alumina (diameter 10 μm) were mixed at 150° C. and heated for 30 minutes to prepare a premixed solution;

[0023] S2: 100 parts of carbon fiber soft felt (thickness 2mm, carbon fiber diameter 2um, density 0.2g / cm 3) After being compressed by 50%, the premixed liquid is infused into the compressed carbon fiber soft felt by using a vacuum-assisted infusion method at high temperature (150°C);

[0024] S3: The soft felt after infusion is further compressed to 20% of its original size at high temperature (150°C), and after cooling to room temperature, the compression mold is released to obtain a carbon fiber reinforced thermal conductive phase change composite material with a thickness of about 0.4 mm.

[0025] Furthermore, the original thickness of the carbon fiber soft felt is 0.5-20 mm, preferably 1-10 mm.

[0026] In the present invention, the carbon fiber felt is significantly different from the carbon fiber used in the prior art. Specifically, the carbon fiber felt used in the present invention has a relatively long carbon fiber, and the overall structure is similar to the non-woven felt network, and the internal arrangement is non-anisotropic; the carbon fibers in the carbon fiber felt of the present invention are arranged transversely and in-plane, which play a role in mechanical enhancement, increasing thermal conductivity and heat dissipation, and preventing pumping out. The carbon fiber used in the prior art is relatively short and does not have an overall network structure.

[0027] In addition, the present invention uses carbon fiber felt to increase the continuity of the carbon fiber network, enhance the Z-direction thermal conductivity while increasing the in-plane thermal conductivity, significantly improving the tensile properties of the original phase change material, the creep effect and preventing pumping out.

[0028] The present invention uses spherical alumina as a thermal conductive additive, which has better insulation properties than aluminum powder; by adding thermoplastic elastomers to adjust the mechanical and flow characteristics of the phase change material, it has better strength and pump-out and creep resistance. The present invention has an innovative structure, using a carbon fiber felt network, an internal phase change material and an alumina ternary structure. The resulting carbon fiber reinforced thermal conductive phase change composite material has high thermal conductivity, high tensile stress, good compressibility and high reliability, effectively solving the pump-out and creep problems of traditional PCM, meeting the needs of high-power integrated circuit heat dissipation, and has the potential to be widely used in servers, communications, military industry, aerospace and other fields.

[0029] Beneficial Effects

[0030] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0031] (1) The composite material of the present invention significantly improves the thermal conductivity of PCM by introducing thermal conductive fillers such as high thermal conductivity carbon fiber soft felt and spherical alumina. At the same time, the addition of thermoplastic elastomer enhances the mechanical properties and shape stability of the composite material, while the introduction of antioxidant effectively improves the thermal oxidation stability of the material, making it less prone to aging and performance degradation during long-term use.

[0032] (2) The composite material of the present invention adopts a unique preparation process, and a premixed liquid is prepared by mixing phase change material, polyolefin elastomer, antioxidant and thermal conductive filler at high temperature, and then the premixed liquid is evenly distributed in the carbon fiber soft felt by vacuum or high pressure assisted infusion technology, and finally the final product is formed by high temperature compression and cooling process. The obtained carbon fiber reinforced thermal conductive phase change composite material has high thermal conductivity, high tensile stress, good compressibility and high reliability, effectively solves the pumping and creep problems of traditional PCM, meets the heat dissipation requirements of high power integrated circuits, and has the potential for wide application in servers, communications, military industry, aerospace and other fields.

[0033] (3) The carbon fiber reinforced thermal conductive phase change composite material of the present invention, due to its unique formula and preparation method, not only has high thermal conductivity and good mechanical properties, but also has no obvious pumping out and creep problems after long-term use. It is suitable for high-power integrated circuit heat dissipation, servers, communications, military industry, aerospace and other fields.

[0034] (4) The carbon fiber reinforced thermal conductive phase change composite material of the present invention has low surface roughness and low interface thermal resistance. The carbon fiber reinforced thermal conductive phase change composite material of the present invention has the characteristics of high tensile strength, anti-slag and chipping, and will not obviously pump out or creep after long-term use, and has good reliability. The carbon fiber reinforced thermal conductive phase change composite material of the present invention is conducive to electronic mounting process and automation, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 The present invention is a flow chart for preparing the carbon fiber reinforced thermal conductive phase change composite material. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] The raw materials in the embodiments and comparative examples were purchased from the following manufacturers and brands:

[0040] Paraffin wax: PetroChina Kunlun brand fully refined paraffin wax

[0041] Polyolefin elastomer: POE, LG LC175

[0042] Antioxidant 1010: Macklin, P750268 Antioxidant 1010

[0043] Spherical alumina: Shanghai Baitu High-tech Materials Technology Co., Ltd., BAK series

[0044] Carbon fiber soft felt: Hangzhou Weiken New Material Technology Co., Ltd., carbon fiber soft felt VU-SF-HP.

[0045] (I) Embodiment

[0046] Embodiment 1:

[0047] A carbon fiber reinforced thermal conductive phase change composite material, the preparation steps of which include:

[0048] S1: 30 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 50 parts of spherical alumina (diameter 10 μm) were mixed at 150° C. and heated for 30 minutes to prepare a premixed solution;

[0049] S2: 100 parts of carbon fiber soft felt (thickness 2mm, carbon fiber diameter 2um, density 0.2g / cm 3 ) After being compressed by 50%, the premixed liquid is infused into the compressed carbon fiber soft felt by using a vacuum-assisted infusion method at high temperature (150°C);

[0050] S3: The soft felt after infusion is further compressed to 20% of its original size at high temperature (150°C), and after cooling to room temperature, the compression mold is released to obtain a carbon fiber reinforced thermal conductive phase change composite material with a thickness of about 0.4 mm.

[0051] Comparative Example 1:

[0052] A carbon fiber reinforced thermal conductive phase change composite material, the preparation steps of which include:

[0053] S1: at 150°C, 30 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 50 parts of thermal conductive filler spherical alumina (diameter 10 μm) were mixed and heated for 30 minutes to prepare a premixed solution;

[0054] S2: After the premixed liquid is vacuumed to remove bubbles, it is cooled to room temperature and the compression mold is released to obtain a thermally conductive phase change composite material with a thickness of about 0.4 mm.

[0055] Comparative Example 2:

[0056] The only difference from Example 1 is that no polyolefin elastomer is added in step S1.

[0057] Comparative Example 3:

[0058] The only difference from Example 1 is that spherical alumina is not added in step S1.

[0059] Comparative Example 4:

[0060] The only difference from Example 1 is that no antioxidant 1010 is added in step S1.

[0061] Comparative Example 5:

[0062] The only difference from Example 1 is that the spherical aluminum oxide in step S1 is replaced by aluminum powder.

[0063] Comparative Example 6:

[0064] The only difference from Example 1 is that the spherical aluminum oxide in step S1 is replaced by zinc oxide.

[0065] Comparative Example 7:

[0066] The difference from Example 1 is that the carbon fiber soft felt is replaced by carbon fiber short fibers. The details are as follows:

[0067] S1: 30 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 50 parts of spherical alumina (diameter 10 μm) were mixed at 150° C. and heated for 30 minutes to prepare a premixed solution;

[0068] S2: 100 carbon fiber staple fibers are laid flat (thickness 2 mm, carbon fiber staple fiber size is 2 um in diameter, 5 mm in length, density 0.2 g / cm 3 ) After being compressed by 50%, the premixed liquid is infused into the compressed carbon fiber short fibers by vacuum-assisted infusion at high temperature (150°C);

[0069] S3: The soft felt after infusion is further compressed to 20% of its original size at high temperature (150°C), and after cooling to room temperature, the compression mold is released to obtain a carbon fiber reinforced thermal conductive phase change composite material with a thickness of about 0.4 mm.

[0070] Comparative Example 8:

[0071] The only difference from Example 1 is that the proportion of the components in step S1 is 50 parts of paraffin wax, 3 parts of polyolefin elastomer, 2 parts of antioxidant 1010 and 30 parts of thermal conductive filler alumina (diameter 10 um).

[0072] (II) Performance test

[0073] Thermal conductivity and application thermal resistance: tested according to ASTM D 5470 standard;

[0074] Tensile stress: tested according to ASTM D 412 standard;

[0075] Compressive stress: Tested according to ASTM D695 standard.

[0076] The carbon fiber thermal conductive phase change composite material prepared in Example 1 exhibits good heat dissipation capability. The thermal resistance is 0.04Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is less than 1um; the tensile stress is greater than 5mPa, and excellent tear resistance and creep resistance. The slag phenomenon is significantly improved. In Example 1, after the introduction of carbon fiber, the heat dissipation capacity of the thermal conductive phase change material is better, the tensile stress is significantly improved, the material stability is better, the compression resistance, slag and chip removal, and the creep resistance are improved. It meets the heat dissipation needs of high-end chips and high-power servers, military industry, aerospace and other fields.

[0077] The thermally conductive phase change composite material prepared in Comparative Example 1 exhibits a normal heat dissipation capability. The measured thermal resistance is 0.08Kcm under a pressure of 40psi. 2 / W; poor mechanics, average surface roughness is less than 1um; tensile stress is 0.8mPa, and tear and creep resistance are poor. In comparative example 1, without the introduction of carbon fiber, the heat dissipation capacity of the thermal conductive phase change material is average, the tensile stress is low, the material stability is poor, it is not resistant to compression, and the creep resistance is poor. It cannot meet the further heat dissipation needs of high-end chips, high-power servers, military industry, aerospace and other fields.

[0078] The thermally conductive phase change composite material prepared in Comparative Example 2 exhibits good heat dissipation capability. The thermal resistance is 0.05Kcm under a pressure of 40psi. 2 / W; better surface roughness, but poor mechanics, and the average surface roughness is less than 1um; the tensile stress is significantly deteriorated compared to Example 1, only about 3mPa, and has very poor tear resistance and creep resistance. The slag phenomenon is obvious. In the absence of thermoplastic elastomer, the heat dissipation capacity of the thermal conductive phase change material is similar, but the tensile stress is significantly reduced, the material stability is worse, it is not resistant to compression, and it slags and chips, and the creep resistance effect is deteriorated. It cannot meet the heat dissipation needs of high-end chips and high-power servers, military industry, aerospace and other fields.

[0079] The thermally conductive phase change composite material prepared in Comparative Example 3 exhibits good heat dissipation capability. The thermal resistance is 0.4Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is less than 1um; tensile stress is greater than 5mPa, excellent tear resistance and creep resistance. The slag phenomenon is significantly improved. In the absence of spherical alumina, the heat dissipation capacity of the thermal conductive phase change material is significantly worse, and the thermal conductivity is poor. It cannot be used as a thermal interface material to meet the heat dissipation needs of high-end chips and high-power servers, military industry, aerospace and other fields.

[0080] The thermally conductive phase change composite material prepared in Comparative Example 4 exhibits good heat dissipation capability. The thermal resistance is 0.04Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is less than 1um; tensile stress is greater than 5mPa, excellent tear resistance and creep resistance. The slag phenomenon is significantly improved. However, without the addition of antioxidants, the material stability deteriorates, the material reliability is poor, and it cannot be used for a long time. It does not meet the needs of high-end chips, high-power servers, military industry, aerospace and other fields.

[0081] The thermally conductive phase change composite material prepared in Example 5 exhibits good heat dissipation capability. The thermal resistance is 0.05Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is less than 1um; tensile stress is greater than 5mPa, excellent tear resistance and creep resistance. The slag phenomenon is significantly improved. However, its insulation performance is significantly lower than that of adding alumina. In addition, the cost of aluminum powder is generally more than double that of alumina, and the heat dissipation and insulation performance are worse.

[0082] The thermally conductive phase change composite material prepared by comparative example 6 exhibits a general heat dissipation capability. The thermal resistance is 0.07Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is less than 1um; tensile stress is greater than 5mPa, excellent tear resistance and creep resistance. The slag phenomenon is significantly improved. After zinc oxide replaces aluminum oxide, the heat dissipation capacity of the thermal conductive phase change material is worse, and other properties are similar. It cannot meet the heat dissipation needs of high-end chips and high-power servers, military industry, aerospace and other fields.

[0083] The thermally conductive phase change composite material prepared by comparative example 7 exhibits good heat dissipation capability. The thermal resistance is 0.06Kcm under a pressure of 40psi. 2 / W; excellent mechanical and surface roughness, and the average surface roughness is about 5um; the tensile stress is 2mPa, and the tear and creep resistance are poor. The slag phenomenon is obvious. After the introduction of carbon fiber staple fibers to replace carbon fiber soft felt, the heat dissipation capacity of the thermal conductive phase change material is worse, the tensile stress is significantly reduced, the material stability is worse, it is not resistant to compression, slag and chips fall off, and the creep resistance effect is deteriorated. It cannot meet the heat dissipation needs of high-end chips and high-power servers, military industry, aerospace and other fields.

[0084] The thermally conductive phase change composite material prepared in Example 8 exhibits a general heat dissipation capability. The thermal resistance is 0.2Kcm under a pressure of 40psi. 2 / W; poor mechanical properties and good surface roughness, and the average surface roughness is less than 1um; the tensile stress is about 4mPa, and the tear and creep resistance is poor. The slag phenomenon is obvious. It cannot meet the heat dissipation requirements of high-end chips, high-power servers, military industry, aerospace and other fields.

[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon fiber reinforced thermal conductive phase change composite material, characterized in that: The invention comprises carbon fiber felt, phase change material, thermoplastic elastomer, antioxidant and spherical aluminum oxide.

2. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: The carbon fiber felt is a high thermal conductivity carbon fiber soft felt, and the carbon fiber diameter in the high thermal conductivity carbon fiber soft felt is 1-100 um and the density is 0.1-1 g / cm 3 .

3. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: The phase change material includes at least one of paraffin, microcrystalline paraffin, stearic acid, and octadecylamine.

4. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: The thermoplastic elastomer includes one or more of polyurethane, polyolefin elastomer, polystyrene elastomer and polyamide elastomer.

5. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant AT-10, antioxidant 168, antioxidant 1010 and antioxidant 1076.

6. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: In parts by weight, the composite material comprises 20-120 parts of carbon fiber felt, 10-40 parts of phase change material, 0.5-5 parts of thermoplastic elastomer, 0.05-5 parts of antioxidant, and 10-70 parts of spherical alumina.

7. The carbon fiber reinforced thermal conductive phase change composite material according to claim 1, characterized in that: The size of the spherical alumina is 1-40 um in diameter.

8. A method for preparing a carbon fiber reinforced thermally conductive phase change composite material according to any one of claims 1 to 7, characterized in that: The preparation steps include: S1: mixing phase change material, polyolefin elastomer, antioxidant and thermal conductive filler aluminum oxide in a certain proportion at high temperature to prepare a premixed liquid; S2: After compressing the carbon fiber soft felt by 30-50%, the premixed liquid is infused into the compressed carbon fiber soft felt using a vacuum or high pressure assisted infusion method at high temperature; S3: further compress the poured soft felt to 10-30% of its original size at high temperature; S4: After cooling to room temperature, releasing the compression mold to obtain a carbon fiber reinforced thermal conductive phase change composite material.

9. The method for preparing a carbon fiber reinforced thermal conductive phase change composite material according to claim 8, characterized in that: In steps S1, S2 and S3, the high temperature range is 70-180°C.

10. The method for preparing a carbon fiber reinforced thermal conductive phase change composite material according to claim 8, characterized in that: The original thickness of the carbon fiber soft felt is 0.5-20 mm.